EXTERNAL MARKERS OF THE BUSINESS IMAGE OF THE MODERN POLITICIAN - Міхайлова, Р. Д.; Костюченко, О. В. (Art and Design, 2023)
The purpose of the article is to identify the external factors of image creation, the features of image presentation through form and style markers – the conscious choice of the silhouette of clothes, shoes, hairstyle, makeup, accessories, color scheme and other elements belonging to the field of visualization, art and design. Methodology. The research uses analysis and synthesis, a historical and comparative approach, and typological constructions according to art history criteria of imagery. Results. On the basis of a comprehensive analysis of theoretical positions formed in the areas of sociology, political science, and psychology, the approaches to this problem in the aspect of design – as a project-constructive form, a stylistic solution – are emphasized. The concept of business image is specified on the example of the formation of the appearance of politicians of different countries and ranks, that is, as an image/image. It is summarized that the business/political image: 1) is projected taking into account the specifics of the activity and the external qualities of the person, implementing cognitive, nominative, aesthetic address functions; 2) is created in the mass consciousness purposefully or spontaneously, according to the visual principle, taking into account the semiotic, cognitive, emotional-evaluative, image-aesthetic components, which are transmitted to the outside by verbal, event and contextual channels of percption of subjects of political reality; 3) in compliance with the rules of business protocol, the external elements of the business image change as a result of objective circumstances, current fashion, and the requirements of the time; 4) ensuring the completeness of external image/image markers is the result of project-aesthetic work of professional stylists, image makers, and fashion designers. It is emphasized that the visual perception of a complete image/image and its components: clothes, shoes, hairstyle, accessories, perfumes and cosmetics, along with behavioral signs and an emotional message, makes the strongest impression. Scientific novelty. The characteristics of the business/political image were formed at the theoretical and practical level: the idea of the main markers of designer-stylistic decisions of the image/image of a politician was systematized; the leading trends in the formation of modern business style in the world and in Ukraine were identified and specified. Practical significance. Disclosure of this issue contributes to greater efficiency of image design at both the theoretical and practical levels.